Praxis Participatory Ergonomics: Learning Facilities in Improving the Quality of Learning at Aqobah International School - Solikhin, Muhammad (Proceeding International Conference on Religion, Science and Education, 2022)
The quality of learning in an educational institution is influenced by the availability and support of learning supporting infrastructure. Through the Participatory Ergonomics Praxis (PEP) it can stimulate the active participation of human resources (HR) in its contribution to improving the quality of learning in educational institutions. The purpose of this study was to determine the quality of learning with a participatory ergonomics approach to learning support facilities at Aqobah International School. The method used in this research is descriptive analysis with a qualitative approach. This study uses primary data obtained through interviews with key informants and secondary data in the form of supporting documents or literature relevant to the research. The data analysis technique in this study uses a model from Miles and Hubberman which consists of data reduction, data presentation and drawing conclusions. The results of the study show that: 1) Participatory Ergonomics Praxis (PEP) through learning support facilities encourages the achievement of improving the quality of learning. 2) The application of participatory ergonomics can increase the self-awareness of human resources (HR in educational institutions through their contribution in managing learning infrastructure well. 3) The quality of education can be improved through the support and availability of infrastructure facilities in their administration and their needs in accordance with the principles of the principle -Principles of participatory ergonomics praxis, The results of the study show that: 1) Participatory Ergonomics Praxis (PEP) through learning support facilities encourages the achievement of improving the quality of learning. 2) The application of participatory ergonomics can increase the self-awareness of human resources (HR in educational institutions through their contribution in managing learning infrastructure well. 3) The quality of education can be improved through the support and availability of infrastructure facilities in their administration and their needs in accordance with the principles of the principle -Principles of participatory ergonomics praxis, The results of the study show that: 1) Participatory Ergonomics Praxis (PEP) through learning support facilities encourages the achievement of improving the quality of learning. 2) The application of participatory ergonomics can increase the self-awareness of human resources (HR in educational institutions through their contribution in managing learning infrastructure well. 3) The quality of education can be improved through the support and availability of infrastructure facilities in their administration and their needs in accordance with the principles of the principle -Principles of participatory ergonomics praxis.